TASKS FOR DEVELOPING PERFORMING SKILLS IN THE NATIONAL ORCHESTRA OF MUSICAL INSTRUMENTS - Khamrokulov Naimdjon Bakhronovich (American Journals Publishing, 2025)
The article examines the essential pedagogical and artistic tasks required for developing performing skills in the National Orchestra of Musical Instruments. Special attention is given to technical mastery, ensemble synchronization, stylistic interpretation, improvisational competence, and the cognitive foundations of musical literacy. The study highlights the specific challenges posed by traditional instruments with unique timbral structures and regional playing techniques. It also outlines rehearsal strategies, conductor–performer interaction models, and task-based approaches that contribute to the formation of a professional performance culture. The conclusions emphasize that well-structured training tasks enable musicians to achieve expressive, coordinated, and culturally authentic orchestral performance.
Keywords: National orchestra, performing skills, ensemble coordination, traditional instruments, musical interpretation, stylistic training, rehearsal pedagogy.